Fundamental Problems of Internal Gravity Waves Dynamics in Ocean - Vitaly V. Bulatov; Yury V. Vladimirov (Journal of Basic & Applied Sciences, 2013)
In paper fundamental problems of internal gravity waves dynamics are considered. The solution of this problem is expressed in terms of the Green’s function and the asymptotic representations of the solutions are considered. The uniform asymptotic forms of the internal gravity waves in horizontally inhomogeneous and non-stationary stratified ocean are obtained. A modified spatio-temporal ray method is proposed, which belongs to the class of geometrical optics methods (WKBJ method). Analytical and numerical algorithms of internal gravity wave calculations for the real ocean parameters are presented.